KAJIAN PENGGUNAAN BETON PRACETAK PADA PROYEK PEMBANGUNAN RUSUNAWA (Studi Kasus Pembangunan Rusunawa POLDA JATIM-Surabaya) - Sugiharti , (Prokons: Jurnal Teknik Sipil, 2014)
The use of precast concrete is planned on work structure tie beam, columns, beams, and slab for precast systems have the advantage in terms time and cost efficiency compared to conventional systems (cast in place) to reach the targets that have been planned by the government.The purpose is to find out the cost efficiency and time usage precast. The cost analysis was obtained from the multiplication of bill of quantity and the work volume. To find a network using the Precedence Diagram Method (PDM) which was processed through Microsoft Project 2007 software then arranged in Bar Chart. The Bar Chart was arranged in the S-Curve with Microsoft Excel 2007 software. From the calculations, total project cost is IDR 13,300,074,303.07 with the cost efficiency IDR 604,137,428.00 or 4.34% less than the conventional method and the duration is 214 days with the time efficiensy 86 workdays or 28.67% quicker than the conventional method.Keywords: pre-cast concrete, cost, time, efficiency